Pelatihan Pembuatan Akun Media Sosial Bisnis Pada Penenun Ulos di Desa Sigaol Kecamatan Uluan, Kabupaten Toba - Romindo M Pasaribu; Vinsensius Matondang; Bilson Pandiangan (Institut Teknologi dan Bisnis Semarang, 2025)
Ulos cloth is a piece of woven fabric from handicrafts made by women with various patterns and rules. In making ulos, it is done in the same way, but the difference is the name, style or moitf and the nature of the position of its use adjusted to the type of traditional ceremony. Social media and marketing through social media is very important for SMEs because the operational costs of using social media are relatively low. Social media has the potential to help Micro, Small and Medium Enterprises (MSMEs) in marketing goods and services. The purpose of this training is to invite and train Ulos weavers in Sigaol Porsea Village in utilizing social media as a medium for marketing and promoting the ulos produced. The social media used are Facebook and Instagram. The result of this training is that Ulos weavers in Sigaol Porsea Village began to understand the benefits of social media marketing such as Facebook and Instagram and will use it as a promotional and marketing media Marketing using social media is one of the marketing strategies that can be used by MSME actors to build networks via the internet. Thus, Ulos weavers in Sigaol village can reach a wider market in marketing the Ulos weaving produced.